a)(x+3)²+(x-1)²-2x²=x²+6x+9+x²-2x+1-2x²
=4x+10
=2(2x+5)
b)(2x+7)²-(3x+5)²+(2x+5)(2x-5)=4x²+28x+49-9x²+30x+25+4x²-25
=-x²+58x+49
c)(x-4)²-(x-3)(x+3)+2(x+1)²=x²-8x+16-x²+9+2(x²+2x+1)
=-8x+25+2x²+4x+2
=2x²-4x+27
d)(2x-3)²-4(x-6)(x+6)-(x-9)(x+9)+x²=4x²-12x+9-4x+144-x²+81+x²
=4x²-16x+234
e)(5x-1)(5x+1)-(4x+3)²+2(3x-1)²=25x²-1-16x²-24x-9+2(9x²-6x+1)
=25x²-1-16x²-24x-9+18x²-12x+2
=27x²-36x-8
f)(3+2x)²-(x+2)(x-2)+4(x-3)²=9+12x+4x²-x²+4+4(x²-6x+9)
=9+12x+3x²+4+4x²-24x+36
=7x²-12x+49
g)(6x-1)²-9(x-1)(x+1)+3(2x-7)²=36x²-12x+1-9x²+9+3(4x²-28x+49)
=27x²-12x+10+12x²-84+147
=39x²-12x+73